Career Identity Development of Photography Majors: The Mediating Role of Photographic Imagination and Creative Self-Efficacy - Wang, Yuanxin (Journal of Research in Vocational Education, 2025)
This study explores how university photography students envision their future careers. We’re interested in understanding their thoughts and feelings as they plan their professional paths. “Professional identity” describes how someone sees themselves in their work role. For photography students, this often involves balancing two important aspects: their passion for creating meaningful art, and the practical need to make a living. Our research suggests two key elements play a vital role in this process. First is “photographic imagination”–the ability to envision and create photos that are not just technically good, but also carry meaning and emotion. Second is “creative self-efficacy”–the fundamental belief in one’s ability to create valuable work. These two elements–imagination and confidence–work together like a bridge. They help students transform classroom learning into a clear, personal vision for their professional future. By sharing these insights, we hope to help educators better support photography students in developing both their artistic voice and their career path.